High antiviral effects of hibiscus tea extract on the H5 subtypes of low and highly pathogenic avian influenza viruses - BAATARTSOGT, Tugsbaatar (J Vet Med Sci, 2016)
Viral neuraminidase inhibitors are widely used as synthetic anti-influenza drugs for the prevention and treatment of influenza. However, drug-resistant influenza A virus variants, including H5N1 highly pathogenic avian influenza viruses (HPAIVs), have been reported. Therefore, the discovery of novel and effective antiviral agents is warranted. We screened the antiviral effects of 11 herbal tea extracts (hibiscus, black tea, tencha, rosehip tea, burdock tea, green tea, jasmine tea, ginger tea, lavender tea, rose tea and oak tea) against the H5N1 HPAIV in vitro. Among the tested extracts, only the hibiscus extract and its fractionated extract (frHibis) highly and rapidly reduced the titers of all H5 HPAIVs and low pathogenic AIVs (LPAIVs) used in the pre-treatment tests of Madin–Darby canine kidney (MDCK) cells that were inoculated with a mixture of the virus and the extract. Immunogold electron microscopy showed that anti-H5 monoclonal antibodies could not bind to the deformed H5 virus particles pretreated with frHibis. In post-treatment tests of MDCK cells cultured in the presence of frHibis after infection with H5N1 HPAIV, the frHibis inhibited viral replication and the expression of viral antigens and genes. Among the plants tested, hibiscus showed the most prominent antiviral effects against both H5 HPAIV and LPAIV.